The Legal, Ethical, and Cultural Issues of Xenotransplantation in Iran: Legal, Ethical, and Cultural Issues of Xenotransplantation - Kazemi, Abdollhasan; Mahmoudi, Soraya; Ehsandoust, Nasrin (Bioethics and Health Law Journal (BHL), 2022)
Background and Aim: Xenotransplantation is a question of "ethics between man and animal". Organ transplantation must be viewed concerning the prevailing cultural, religious, and socioeconomic conditions of a nation. The major limitation to applying xenotransplantation for the treatment of disease is a shortage of human donors. We may come up with the question of whether xenotransplantation in Iran is practical or if we will have legal, ethical, and cultural problems. Methods: This research is analytical- descriptive. We first discuss xenotransplantation and its effect on it human rights and human dignity and animal rights in Islam. Then, we will explain the personal, social, and cultural effects of xenotransplantation in Iran, the ethical response to this issue, and the necessity of legislation about xenotransplantation in Iran. Ethical Considerations: Ethical principles were considered in searching and citing the literature. Results: In recent years, the necessity of xenotransplantation has increased and thousands of men, women, and children suffer from end-stage organ failure in Iran. Regarding this, the present study evaluated Xenotransplantation with attention to animal rights in Islam, laws, ethical and legal state, and religious and cultural beliefs in Iran. In Iran, there are no special laws about this issue and there is just research guideline for researchers that it is not enough and complete. It will cause problems for patients who need essential transplant operations. Conclusion: Although a comprehensive investigation of this issue has not been accomplished, we can find problems with paying attention to legal and religious beliefs in society. *Corresponding Author: Soraya Mahmoudi; Email: msoraya9591@yahoo.com; ORCID: https://orcid.org/0000-0002-3399-1360 Please cite this article as: Kazemi A, Mahmoudi S, Ehsandoust N. The Legal, Ethical, and Cultural Issues of Xenotransplantation in Iran. Bioeth Health Law J. 2022; 2(1):1-5 (e2). http://doi.org/10.22037/bhl.v2i1.21455